THE MOTIF OF FREEDOM IN MARK TWAIN’S NOVELS ("Conference on Universal Science Research 2023", 2025)
This thesis examines the motif of freedom in the novels of Mark Twain, focusing on how the author explores personal, social, and moral freedom through his characters and narratives. Twain presents freedom not only as physical escape but also as liberation from social hypocrisy, racial injustice, and rigid moral norms. By analyzing The Adventures of Tom Sawyer, Adventures of Huckleberry Finn, and A Connecticut Yankee in King Arthur’s Court, this study demonstrates that freedom is a central value in Twain’s literary vision and a key element of his criticism of American society in the nineteenth century.